2019
DOI: 10.1002/wps.20609
|View full text |Cite
|
Sign up to set email alerts
|

The evidence‐based group‐level symptom‐reduction model as the organizing principle for mental health care: time for change?

Abstract: The content and organization of mental health care have been heavily influenced by the view that mental difficulties come as diagnosable disorders that can be treated by specialist practitioners who apply evidence-based practice (EBP) guidelines of symptom reduction at the group level. However, the EBP symptom-reduction model is under pressure, as it may be disconnected from what patients need, ignores evidence of the trans-syndromal nature of mental difficulties, overestimates the contribution of the technica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
143
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 172 publications
(153 citation statements)
references
References 95 publications
6
143
0
4
Order By: Relevance
“…Adolescent respondents preferred a warm, relatable, empathic, and non-judgmental counsellor who ensured confidentiality, and provided a safe and private space for adolescents to share their problems. This is consistent with a large body of international research demonstrating the primary importance paid by young people (and service users more generally) to 'non-specific' relational aspects of mental health care (Butler, 2007;Persson et al 2016;Van Os et al 2019). Relatedly, studies from high-income countries have shown that face-to-face therapy may be preferred by adolescents over pure self-help and remotely delivered formats (Farrand et al 2006;Bradford & Rickwood, 2014).…”
Section: Discussionsupporting
confidence: 79%
“…Adolescent respondents preferred a warm, relatable, empathic, and non-judgmental counsellor who ensured confidentiality, and provided a safe and private space for adolescents to share their problems. This is consistent with a large body of international research demonstrating the primary importance paid by young people (and service users more generally) to 'non-specific' relational aspects of mental health care (Butler, 2007;Persson et al 2016;Van Os et al 2019). Relatedly, studies from high-income countries have shown that face-to-face therapy may be preferred by adolescents over pure self-help and remotely delivered formats (Farrand et al 2006;Bradford & Rickwood, 2014).…”
Section: Discussionsupporting
confidence: 79%
“…Although being positive, clinicians considered the guidelines less useful for treatment selection, assessment of patients' prognosis, communication with other health professionals and education of patients and their relatives about their condition. This finding is in line with the field trials carried out for the development of ICD-10, DSM-IV, and DSM-5 [3] and could be due to the fact that many psychiatric treatments are trans-nosographic and are not guided only by patients' diagnosis [21,44]. Nevertheless, clinicians' ratings on the usefulness of the ICD-11 diagnostic guidelines for treatment selection, prognosis, and communicating with patients and families were substantially higher compared to those reported by clinicians using the ICD-10, the DSM-IV or the DSM-5 [3].…”
Section: Discussionsupporting
confidence: 81%
“…Over the years, there have been many debates about what outcomes we should focus on. Some have questioned the symptom-reduction model, and argued that the focus should be on transsyndromal symptom reduction such as resilience and social participation (Os, Guloksuz, Vijn, Hafkenscheid, & Delespaul, 2019).…”
Section: What Should the Treatment Affect?mentioning
confidence: 99%